Validation of urinary biomarkers for accurate diagnosis of urinary tract infections in older adults across primary care, hospitals and long-term care facilities in the Netherlands and UK (UTI-GOLD): a multicentre observational study protocol - Simon P Mooijaart; Simon P Conroy; Abimbola A Akintola; Wilco P Achterberg; Janneke E Stalenhoef; Cees van Nieuwkoop; Jelle J Goeman; Christa M Cobbaert; Paul L A M Corstjens; Martijn Sijbom; Martha T van der Beek; Leo G Visser; et al. (BMJ Open, 2025)
Introduction Urinary tract infections (UTIs) are highly prevalent and pose a significant burden among older adults. Accurate diagnosis in this population is challenging due to the high prevalence of pre-existing lower urinary tract symptoms, inability to express symptoms and asymptomatic bacteriuria. Current diagnostic tests are unreliable, often resulting in over- and underdiagnosis. A previous pilot study proposed a higher cut-off for pyuria and identified five promising biomarkers for the diagnosis of UTIs in older adults. The UTI-GOLD study aims to validate these five new biomarkers and the higher leucocyte cut-off as a diagnostic tool for UTIs in older people in a real-world setting.Methods and analysis Between August 2024 and December 2027, an observational multicentre diagnostic accuracy study is being conducted across primary, secondary and tertiary healthcare facilities in the Netherlands and the UK. Adults ≥65 years with a suspected UTI will be considered eligible. Patients with pre-existing decision-making incapacity or an indwelling catheter will be excluded. UTI will be defined according to an international consensus-based reference standard. Biomarkers will be measured by liquid chromatography-mass spectrometry (neutrophil gelatinase-associated lipocalin, tissue inhibitor of metalloproteinase 2 and CXC motif chemokine ligand 9) and enzyme-linked immunosorbent assay (interleukin 6 and azurocidin). Pyuria will be quantified by automated microscopy and/or flow cytometry. Diagnostic accuracy measures will be calculated using the receiver operating characteristic curves, and sensitivity, specificity, likelihood ratios and predictive values will be reported for optimal cut-offs.Ethics and dissemination The protocol was reviewed by the local Leiden University Medical Center research committee, who declared on 15 April 2024 that the medical research involving human subject act (Dutch abbreviation: WMO) does not apply to the current study (reference number nWMODIV2_2024025). The study also received approval from the NHS Research Ethics Committee in the UK (reference number 24/LO/0649).The study findings will be published in a peer-reviewed journal, presented at academic congresses and shared with healthcare providers.Trial registration number The study was registered at clinicaltrial.gov on the 24 September 2024 with registration number: NCT06610721.